Covid-19 pandemic: factors affect retention among students during online learning? - Sow, Alston Kah Hoong; Cheng, Ai Nee; Foong, Pooi Yee; You, Xi Na (2022)
The purpose of this study was to determine the impact of institutional support, behavioral characteristics, and quality of faculty and student interaction on student retention. This study was also used to verify whether the student retention rate would increase due to the influence of these three independent variables. The study was conducted by distributing online questionnaires to students at Universiti Tunku Abdul Rahman, Monash University, INTI University Nilai and Taylor University via google form questionnaire. The data retrieved from the online surveys will be processed with the aid of Microsoft Excel and Statistical Package for Social Science (SPSS) in order to produce accurate results for the purpose of analysis and interpretation. In this case, the data will be analysed according to reliability tests, descriptive analysis, Pearson correlation, and Multiple regression analysis. Finally, institutional support, behavioral characteristics, and quality of faculty and student interaction had significant effects on student retention, and an increase in any of these independent variables would increase student retention. There are a few studies that are consistent with the results and are therefore further elaborated in Chapter two of our study.